SBA-15 Pelletisation - Data Set - Wadi, Basil; Nabavi, Seyed Ali; Manovic, Vasilije (Cranfield University, 2021)
Data set accompanying article to be published in Powder technology titled: Formulation, Adsorption Performance, and Mechanical Integrity of Triamine Grafted Binder-Based Mesoporous Silica Pellets for CO2 Capture.
Keywords: 'adsorption'; 'sba-15'; 'pellets'; 'Amine'; 'Functionalisation'; 'Carbon Capture Engineering (excl. Sequestration)'